2015
DOI: 10.1002/etc.2948
|View full text |Cite
|
Sign up to set email alerts
|

Observed and modeled effects of pH on bioconcentration of diphenhydramine, a weakly basic pharmaceutical, in fathead minnows

Abstract: A need exists to better understand the influence of pH on the uptake and accumulation of ionizable pharmaceuticals in fish. In the present study, fathead minnows were exposed to diphenhydramine (DPH; disassociation constant = 9.1) in water for up to 96 h at 3 nominal pH levels: 6.7, 7.7, and 8.7. In each case, an apparent steady state was reached by 24 h, allowing for direct determination of the bioconcentration factor (BCF), blood-water partitioning (PBW,TOT), and apparent volume of distribution (approximated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
80
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 80 publications
16
80
1
2
Order By: Relevance
“…Though the sampling location of the present study was downstream of a large ($200 million gallons per day) WWTP effluent discharge, effluent exposure was decreased by elevated dilution in Buffalo Bayou compared with our previous findings in effluent-dependent wadeable streams [2,28,31,41]. In addition, surface and bottom water salinity and pH vary spatially (upstream, downstream, and vertically) and temporally [11], which strongly affects uptake of ionizable pharmaceuticals (discussed below) across fish gills [28,42,43]. It also may be that bioaccumulation differences among some compounds reported in Tables 3 and 4 resulted from fish species predominantly occupying freshwater or saltwater habitats.…”
Section: Accumulation Of Pharmaceuticals In Fishcontrasting
confidence: 45%
See 1 more Smart Citation
“…Though the sampling location of the present study was downstream of a large ($200 million gallons per day) WWTP effluent discharge, effluent exposure was decreased by elevated dilution in Buffalo Bayou compared with our previous findings in effluent-dependent wadeable streams [2,28,31,41]. In addition, surface and bottom water salinity and pH vary spatially (upstream, downstream, and vertically) and temporally [11], which strongly affects uptake of ionizable pharmaceuticals (discussed below) across fish gills [28,42,43]. It also may be that bioaccumulation differences among some compounds reported in Tables 3 and 4 resulted from fish species predominantly occupying freshwater or saltwater habitats.…”
Section: Accumulation Of Pharmaceuticals In Fishcontrasting
confidence: 45%
“…A recent study by our research team extended this effort to examine pH influences on whole-body bioaccumulation of the ionizable weak base diphenhydramine in the fathead minnow [43]. Nichols et al [43] observed the apparent volume of distribution (V d ) for diphenhydramine in fathead minnows (3 L/kg) to be almost identical to V d in humans (3-8 L/kg), which further highlights the potential for biological "read-across" with human pharmacological and toxicological data [18,45,[49][50][51][52]. Such observations further indicate that V d , in addition to clearance, is more relevant to predict bioaccumulation of ionizable contaminants than traditional log octanol-water partition coefficient-based modeling efforts with lipid normalization for nonionizable chemicals.…”
Section: Accumulation Of Pharmaceuticals In Fishmentioning
confidence: 99%
“…For example, Winter et al (2008) found that the measured and predicted plasma concentrations for atenolol in fathead minnow based on water exposure in the laboratory were within a factor of 2 using the same equation as used in the present study. Other studies showing close agreement between observed and predicted plasma concentrations from water exposure in the laboratory include Garcia et al (2012), Valenti et al (2012), Nichols et al (2015), and Nallani et al (2016b). In some cases predicted values were far less than those observed for fish collected in the field.…”
Section: Introductionmentioning
confidence: 58%
“…Several authors have utilized this equation for ionizable pharmaceuticals (Du et al 2014; Tanoue et al 2015; Nichols et al 2015), which was developed in the laboratory using water-only in vivo exposures and in vitro equilibrium after injection. A factor of 0.16 accounts for the fraction of organic material in trout blood (Nichols et al 2015), which we assumed was similar to that for Chinook salmon. Log Pbw=logfalse(false(100.73italiclogDow0.16false)+0.84false)…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is likely to think that other mechanisms (rather than lipophilicity), such as receptor-binding interactions or differences in the biotransformation rates, may be involved in the accumulation of polar pharmaceuticals in fish (Ramirez et al, 2009;Tanoue et al, 2014). Nichols et al (2015) studied the effect of pH on waterborne diphenhydramine (a weak base) bioconcentration by fathead minnows. Authors found that the ionized fraction of the pharmaceutical contributes substantially to the observed distribution of total pharmaceutical between blood and tissues and that some factor other than lipid content controls its distribution, suggesting it could be its binding to tissue proteins (exceeding its binding to plasma proteins) as well as considering effects at the gill surface (acidification).…”
Section: Compoundmentioning
confidence: 99%